Geomagnetic disturbance effects on satellite attitude estimation. (March 2021) - Cilden-Guler, Demet; Kaymaz, Zerefsan; Hajiyev, Chingiz
Abstract: This study investigates the effects of magnetic disturbances resulting from geospace storms on the satellite attitudes estimated by EKF. It is shown that the increasing levels of geomagnetic activity affect geomagnetic field vectors predicted by IGRF and T89 models. Various sensor combinations including magnetometer, gyroscope, and sun sensor are evaluated for magnetically quiet and active conditions. Errors are calculated for estimated attitude angles and differences were discussed. This study emphasizes on the importance of environmental factors on the satellite attitude determination systems. Highlights: Focuses on using an empirical model for global magnetosphere in attitude estimation. Estimates the attitude angles with smaller errors when using T89 during active days. Emphasizes on the effects of the geomagnetic disturbances on the attitude angles. Helps to choose sensor combination during quiet/disturbed times for better attitude.